Diversity of Insect Species in Generative Phase Maize Plant in Caturharjo, Sleman - Fatihatuljannah Adz-Dzikir; Ichsan Luqmana Indra Putra (Institut Pertanian Bogor, 2026)
The presence and diversity of these insects are influenced by insect activity. This study aimed to analyze the diversity and dominance of insect species in the generative phase of maize fields in Caturharjo Village, Sleman, Yogyakarta. The research was conducted from March to August 2025, on a 1000 m2 maize field. The maize field was then divided into three plots, each measuring 10 × 15 m. One light trap was set at the center of each plot. Insects were collected every three days. Insect species diversity was calculated using the Shannon–Wiener Index, and species dominance was calculated using the Simpson Index. Data on the abundance of individuals and abiotic factors were then analyzed using a correlation test. The results obtained 60 species of insects in the maize generative phase in Caturharjo Village. The highest number of insect individuals found was Paederus fuscipes (1272 individuals), which had the highest role of insects as predators (31.67%). The index value of species diversity obtained in this study fell into the medium category (H' = 1.1484), and there were no dominant species of insects at the research site (D = 0.1093). The conclusion of this study is that there are 60 species of insects at the study site, with a moderate level of diversity and no dominant species in the study site. Keywords: Anoplolepis gracillipes, insect, maize, Paederus fuscipes, predator